2014
DOI: 10.1093/nar/gku1021
|View full text |Cite
|
Sign up to set email alerts
|

RNA-dependent chromatin localization of KDM4D lysine demethylase promotes H3K9me3 demethylation

Abstract: The JmjC-containing lysine demethylase, KDM4D, demethylates di-and tri-methylation of histone H3 on lysine 9 (H3K9me3). How KDM4D is recruited to chromatin and recognizes its histone substrates remains unknown. Here, we show that KDM4D binds RNA independently of its demethylase activity. We mapped two non-canonical RNA binding domains: the first is within the N-terminal spanning amino acids 115 to 236, and the second is within the C-terminal spanning amino acids 348 to 523 of KDM4D. We also demonstrate that RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 45 publications
(51 reference statements)
2
30
0
Order By: Relevance
“…Interestingly, it was recently reported that KDM4D is able to bind RNA through two distinct RNA-binding domains, one of which is the JmjC domain. The KDM4D binding to RNA is independent of KDM4D demethylase activity and is required for its association with chromatin [91]. Whether all the JmjC-containing proteins require RNA for their enzymatic activity as well as for their association with chromatin is still unknown and should be clarified by further studies.…”
Section: Kdm4 Cluster (Jmjd2 Subfamily)mentioning
confidence: 95%
“…Interestingly, it was recently reported that KDM4D is able to bind RNA through two distinct RNA-binding domains, one of which is the JmjC domain. The KDM4D binding to RNA is independent of KDM4D demethylase activity and is required for its association with chromatin [91]. Whether all the JmjC-containing proteins require RNA for their enzymatic activity as well as for their association with chromatin is still unknown and should be clarified by further studies.…”
Section: Kdm4 Cluster (Jmjd2 Subfamily)mentioning
confidence: 95%
“…Toward this end, we took advantage of KDM4D-1H4R-HRK mutant that lost its ability to bind RNA molecules and shows defective chromatin localization. 62 Laser microirradiation assay, performed on U2OS cells expressing EGFP-KDM4D-1H4R-HRK mutant, shows no detectable accumulation of the mutant at DNA breakage sites (Fig. 3).…”
Section: Kdm4d-rna Interactions Are Essential For Kdm4d Recruitment Tmentioning
confidence: 96%
“…One possible explanation for these apparently contradictory results is that the defective accumulation of KDM4D-1H4R-HRK at DNA damage sites results from the fact that KDM4D-1H4R-HRK is found in the nuclear soluble fraction but not in the chromatinbound fraction. 62 In other words, 1H4R-HRK mutations exhibit dominant negative effect and suppress the ability of the C-terminal region to recruit KDM4D to damage sites.…”
Section: Kdm4d-rna Interactions Are Essential For Kdm4d Recruitment Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutating His115/ 219, Arg222/225/228/236/123 and Lys127 of KDM4D results in loss of RNA and chromatin binding. 7 This mutant, which can no longer bind RNA, failed to accumulate at DNA damage sites, indicating that KDM4D-RNA interaction is required for its DNA damage accumulation. 6 Altogether, these studies implicate PARP1 and yet unidentified RNA molecules in regulating KDM4D function in the DDR.…”
mentioning
confidence: 97%